Produção de biodiesel de óleo de macaúba por catálise heterogênea - Pasa, Thiago Luiz Belo (2015)
Biofuels are gaining space for presenting features that highlight how environmentally friendly. The biodiesel fits like a biofuel that can replace diesel oil derived from oil. It can be obtained from various raw materials, and its main source of production the triacylglycerides and free fatty acids. The Macaúba (Acrocomia aculeata (Jacq.) Lood. Ex Mart.) Is a native arborescent palm of tropical forests, with wide geographical distribution and large production of oil / ha. Oil Pulp Macaúba has characteristics that enable the production of biodiesel, has a large amount of free fatty acids, hindering the traditional process biodiesel production with basic catalyst. The catalyst most suitable for materials with such characteristics are acid catalysts. In order to reduce contaminants and facilitate the purification process was employed a heterogeneous acid catalyst, the Amberlyst 15, which can also be reused. The oil macaúba pulp, the heterogeneous catalyst, the adsorbent and the biodiesel produced were characterized by official methods provided by the ANP and AOCS and references. The production of biodiesel was held in 4842 Parr reactor using a CCRD planning and 2³ complete. The reaction mixture was ethanol, oil Macaúba pulp and Amberlyst 15, the product followed by washing for purification to give a content of 89% esters and ethyl esters conversion of 86% GLA. In order to improve the wet wash and get results within the specifications required by the ANP, a study of adsorption was carried out by adjusting kinetic models of adsorption isotherms and. The results showed that adsorption takes place within 120 minutes of stabilization and adsorption of free glycerol results are within specification. The production of biodiesel by heterogeneous catalysis using oil Macaúba pulp and Amberlyst 15 proved promising and with results close to expectations of a quality biodiesel.